An evaluative study of the University of San Carlos boys high school guidance program and a proposed career guidance program for the University of San Carlos boys high school seniors - Ipong-de Fiesta, Elena (Animo Repository, 1975)
The first part of this study seeks to determine the extent to which the University of San Carlos Boys High School Guidance Program is effective. The normative survey method was utilized in this study. The techniques used were questionnaires, interviews, and personal observations. The school's organizational chart and guidance flow chart were examined. The guidance personnel and some school staff were interviewed regarding the operations and functions of the guidance department. Three evaluative instruments were adapted for the gathering of data, namely, the Student Inventory of Guidance Awareness, the Teacher Inventory of Guidance Awareness, and the Criteria for Evaluating A School's Guidance Program. It was found that the USC Boys High School Guidance Department had no specific objectives upon which the services were based. The students were aware of the guidance services that were being offered to them, but indicated that they did not get adequate assistance from the guidance department. The teachers however, encouraged students to avail themselves of the guidance services. They also assisted the guidance staff in the administration of guidance services. It was also found that the number of guidance personnel was not enough to meet the needs of the school population. There was found to be a need to expand the guidance office and its facilities as indicated in the suggestions offered by the students and the teachers. The second part of the study aims to establish a career guidance program for the senior students of the USC Boys High School. The normative survey method of research was used for the study. The subjects consisted of 178 seniors of the USC Boys High School enrolled during the school year 1974-75 and 62 parents. The results of the Mooney Problem Checklist as well as the results of the evaluative survey done in the first part of this study were referred to. A questionnaire for the parents and a guide for student interview on the factors which affected the career choices of the students were likewise constructed. The level of significance of difference among the frequencies of the respondents' answers was set at .01 level. The chi square values were computed and the frequencies of the career choices and factors which affected the choices were converted into ranks. The findings of the study showed that the students expressed the greatest preference for Health Occupations, followed by Technical and Engineering, Business and Clerical, and Agriculture. The following factors affected their choice of careers : interest, ability, good of mankind, profit, opportunity to go abroad, family tradition, interest of parents, opportunity for employment, and stepping stone for another course. Parents played a significant role in the career choices of their sons. The information gathered about the needs of the students, and the factors which affected them and their parents in choice of career were used as basis for the formulation of the proposed program's objectives, services and activities.